2020
DOI: 10.3390/foods9111602
|View full text |Cite
|
Sign up to set email alerts
|

Could Global Intensification of Nitrogen Fertilisation Increase Immunogenic Proteins and Favour the Spread of Coeliac Pathology?

Abstract: Fertilisation of cereal crops with nitrogen (N) has increased in the last five decades. In particular, the fertilisation of wheat crops increased by nearly one order of magnitude from 1961 to 2010, from 9.84 to 93.8 kg N ha−1 y−1. We hypothesized that this intensification of N fertilisation would increase the content of allergenic proteins in wheat which could likely be associated with the increased pathology of coeliac disease in human populations. An increase in the per capita intake of gliadin proteins, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…It was hypothesized that the increase in N fertilization could be related to a potential increase of gluten in wheat grains and flours and thus to the spread of CD ( Penuelas et al, 2020 ). They carried out a meta-analysis (1961–2016) and found that the increase in N fertilization rates was associated with increased content of total gluten, including all gliadin fractions, and gliadin transcripts in wheat grains, which provided a strong potential increase in the average human intake of gliadins.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the increase in N fertilization could be related to a potential increase of gluten in wheat grains and flours and thus to the spread of CD ( Penuelas et al, 2020 ). They carried out a meta-analysis (1961–2016) and found that the increase in N fertilization rates was associated with increased content of total gluten, including all gliadin fractions, and gliadin transcripts in wheat grains, which provided a strong potential increase in the average human intake of gliadins.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of soil nutrients can affect soil respiration, but these effects can vary depending on the dose and duration (Cascio et al, 2017). Some ecosystems will be more limited by nitrogen (N), and others will be more limited by phosphorus (P) (Penuelas et al, 2020;Peñuelas et al, 2013), and N and P contents can have interactive effects. These differences depend primarily on the soil, especially its age, and can vary greatly between geographical locations and biome types.…”
Section: Introductionmentioning
confidence: 99%
“…Intensified fertilization with N may increase the allergenic proteins content of wheat, which may be related to the increase in CD pathology. The study that put forward this hypothesis concluded, after a literature meta-analysis, that wheat grown under higher N availability in the soil produces not only higher yield but also grains and flour with higher concentrations of gliadin in all genotypes [225]. However, further experimental studies need to be done, and if this hypothesis stands, we will have an important lead to follow to prevent and control the spread of CD.…”
Section: Gluten-related Misconceptionsmentioning
confidence: 99%